The etiology of bacterial meningitis in children aged 2-60 months diagnosed at queen elizabeth hospital, kota kinabalu: before and after the introduction of hemophilus influenzae (hib) vaccine - Hamid, Asmiati Abd (2007)
Objectives: The objective of this study is to establish a local data about the incidence of Hib meningitis and the effectiveness of Rib vaccination against the disease among children aged 2 to 60 months in Queen Elizabeth Hospital, Kota Kinabalu, Sabah, Malaysia. We also look at the pattern of etiological agents of bacterial meningitis following a routine use of Rib vaccine.Method: This was a retrospective study, conducted at Queen Elizabeth Hospital, Kota Kinabalu, Sabah, Malaysia. All case notes of patients with meningitis admitted before Hib conjugate vaccine introduced from Jan 1999 to Dec 2001 and after the implementation of the vaccine between Jan 2004 to Dec 2006 were evaluated in the study. The patient must be aged between 2 to 60 months at the time of the diagnosis and the diagnosis was confirmed by clinical fmdings and cerebrospinal fluid assessment (CSF). The etiologic agents were based on positive CSF culture and/or latex agglutination test. Clinical information from the case notes, including CSF results and the outcome on discharge, were obtained. Analysis of extracted data was performed using SPSS version 12.0 and STATA. Results: 216 case notes of patients were included in the study, 103 patients before and 113 patients after the introduction of the Hib vaccine. Hib meningitis incidence decreased from 2.27 to 0.3 cases per 100 000 overall population, and from 21 to 2.85 cases per 100 000 population in children less than 5 year. Hib meningitis before the vaccination was 33.0% (95% CI 24.0, 43.0) and after the introduction of the Rib vaccine Rib meningitis significantly reduced to 6.2% (95% CI 2,5, 12.4) (p:<O.OOl). Following the Hib vaccination, the complications were less severe and the mortality from Hib meningitis . was significantly reduced. Pneumococcal meningitis however, was notably increased in frequency from 5.8% before the Hib vaccine period to 18.6% after the implementation of Hib vaccine. Other organisms that caused bacterial meningitis were not affected by the Hib vaccination. Conclusion: The implementation of the Hib vaccine not only reduced the incidence of Hib meningitis but has reduced the incidence of bacterial meningitis as a whole. Patients with Hib meningitis who received Hib vaccination has developed less severe complications and results in less mortality. Pneumococcal meningitis however, alarmingly increased during the period studied.